Research on the association benefits for the agricultural producer market manifestations - Maria Magdalena Turek Rahoveanu; Gheorghe Adrian Zugravu; Cristea Luiza (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 3rd Edition of the International Symposium, October 2012, Bucharest, 2012)
At the current stage, agricultural producers joining in association forms opens up new opportunities for economic development by attracting local, local or regional advantages and using collective power to increase prosperity of members, their families and communities to which they belong. The work is part of the rural development priorities of CAP reform 2014-2020 on the competitiveness of agriculture and farm viability. The new concept of rural development includes actions relating to: a) facilitating restructuring of farms facing major structural problems, particularly farms with low market participation and farms that need agricultural diversification; b) facilitating generations renewal in agriculture. The paper aims to identify the benefits of agricultural association through a survey conducted in 10 counties of Romania in several representative beekeeping cooperatives.
Keywords: 330; Advantages; cooperation; association; producers group